Pandemic, Job loss, Food consumption, Child health: Impact of (COVID-19) on the livelihood of marginal income people in Bangladesh - Mst. Noiyan Tara; Rashed Ahmed; Md. Shamimul Islam; S. M. Atiquzzaman Mulla; Md. Minhaz Uddin (Indonesian Journal of Economics, Social, and Humanities, 2023)
The study is to understand the livelihood-related impact on the marginalized people due to the outburst of the COVID-19 pandemic. This paper also investigates the effects on child health of the vulnerable households who lost their work or job during these crisis moments. Following the fisher sampling method, 348 respondents are interviewed for quantitative and qualitative data. In this study, 20 districts from 7 divisions of Bangladesh are covered. Among the respondents, 90% said that the COVID-19 pandemic negatively impacts their livelihood due to income loss. This study also found that 50% of people (respondents) lost their jobs, and almost 90% of people revealed that their income level declined due to COVID-19. As a result, their dietary patterns changed significantly. Due to inadequate food consumption and marginal income, people face an acute health crisis, especially child health. They declined their food intake, ultimately maintaining their partial expenditure by borrowing from financial institutions and relatives. The empirical evidence shows that job loss and income reductions positively impact raising children's health vulnerability. Since the government did not support them properly, their survival will be threatened in the long run. So, the study shows that COVID-19 affects the daily income and consumption patterns of vulnerable households who live by daily earnings.